Effect of formulation method, lipid composition and PEGylation on vesicle lamellarity: a small-angle neutron scattering study - Nele,V; Holme,M; Kauscher,U; Thomas,MR; Doutch,JJ; Stevens,M (Langmuir, 2019)
Liposomes are well-established systems for drug delivery and biosensing applications. The design of a liposomal carrier requires careful choice of lipid composition and formulation method. These determine many vesicle properties including lamellarity, which can have a strong effect on both encapsulation efficiency and the efflux rate of encapsulated active compounds. Despite this, a comprehensive study on how the lipid composition and formulation method affect vesicle lamellarity is still lacking. Here, we combine small-angle neutron scattering and cryogenic transmission electron microscopy to study the effect of three different well-established formulation methods followed by extrusion through 100 nm polycarbonate membranes on the resulting vesicle membrane structure. Specifically, we examine vesicles formulated from the commonly used phospholipids 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC), 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) via film hydration followed by (i) agitation on a shaker or (ii) freeze–thawing, or (iii) the reverse-phase evaporation vesicle method. After extrusion, up to half of the total lipid content is still assembled into multilamellar structures. However, we achieved unilamellar vesicle populations when as little as 0.1 mol % PEG-modified lipid was included in the vesicle formulation. Interestingly, DPPC with 5 mol % PEGylated lipid produces a combination of cylindrical micelles and vesicles. In conclusion, our results provide important insights into the effect of the formulation method and lipid composition on producing liposomes with a defined membrane structure.